NEURAL NETWORK SYSTEM TRACKS LANDING AIRCRAFT WHEN WIND DIRECTION CHANGES - G. N. Lebedev; V. B. Malygin (Научный вестник МГТУ ГА)
The article describes the problem of solving important practical problems of redistribution of aircraft when landing on a different route of the Moscow air hub in the event of a sudden change of weather conditions. The neural network procedure to set priorities for each aircraft in real time based on dynamic programming is offered. This allowed us to generate lists of vessels for each trace landing and to determine their priority for landing.